PENGARUH RELATIONSHIP MARKETING, CUSTOMER VALUE, DAN TRUST TERHADAP LOYALITAS PELANGGAN PADA PT. ASURANSI JIWASRAYA CABANG KOTA MALANG - Anggrahita Satriyo Wiwoho (Manajemen Bisnis, 2018)
The purpose of this study was to determined the effect of relationship marketing, costumer value, and trust on the customer's loyalty at PT.Jiwasraya Insurance branch of Malang. This study used multiple linear regression analysis and tested on 100 Respodents that have been determined by used purposive sampling technique as a method, and used questionnaires for data collection.The result of this study were concluded that variables such as:1) Relationship marketing significally influenced the customer's loyalty of PT Jiwasraya Insurance branch of Malang. 2) Customer value significally influenced the customer's loyalty of PT Jiwasraya Insurance branch of Malang. 3) Trust was significally influenced the customer's loyalty of PT Jiwasraya Insurance branch of malang.